2015
DOI: 10.1007/s11605-015-2836-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Morphology of Colorectal Liver Metastases after Preoperative Chemotherapy Predicts Tumor Viability and Postoperative Outcomes

Abstract: The CT morphology of CLM predicts tumor viability and long-term surgical outcomes after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 17 publications
1
12
1
Order By: Relevance
“…Interestingly, a significantly longer PFS was observed in patients with optimal morphologic responses, though all 3 patients exhibited an increase in tumor size at the time of the diagnosis of the morphologic response. Although previous studies have confirmed that the morphologic response occurs independently of the size response, [ 4 , 6 , 8 ] given that 40%–60% of patients with the optimal responses also exhibited size-based responses, [ 6 , 8 ] the patterns of response observed in the present study seem to differ from those reported for first-line chemotherapy.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Interestingly, a significantly longer PFS was observed in patients with optimal morphologic responses, though all 3 patients exhibited an increase in tumor size at the time of the diagnosis of the morphologic response. Although previous studies have confirmed that the morphologic response occurs independently of the size response, [ 4 , 6 , 8 ] given that 40%–60% of patients with the optimal responses also exhibited size-based responses, [ 6 , 8 ] the patterns of response observed in the present study seem to differ from those reported for first-line chemotherapy.…”
Section: Discussioncontrasting
confidence: 80%
“…The CT morphologic response to chemotherapy has been reported to be a good prognostic indicator in both medical [ 4 , 11 ] and surgical [ 4 , 6 , 8 ] populations with colorectal liver metastases, especially in patients treated with bevacizumab. The reported strength of a CT morphologic response is that it may predict differences in pathological response “quality,” [ 7 , 13 , 14 ] and a strong correlation between CT morphology and the pathological viability of tumors has been confirmed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The learning curve is short and the interobserver agreement excellent across a wide range of experience. It was recently confirmed by an independent group from Japan 14. The only limitation to the scoring is the image quality.…”
Section: Discussionmentioning
confidence: 85%